FEATURES OF THE FORMATION OF THE DUNGAN LITERARY LANGUAGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the features of the formation of the Dungan literary language through the prism of the theoretical aspects of the issue of literary language and its compliance with the status of a literary language, taking into account the standards adopted in theoretical linguistics and its definitions. It is argued that the modern Dungan literary language it is characterized by the presence of written literature of various genre content, and certain normative reference books and publications, which determines its the status of the literary language.
Keywords: literary language, types of literary languages, codification, regulation, norm, linguistic function, dialect base.